Comparative evaluation conducted on the selection of the type of roller shredder for the cultivation of plowed land - Mamarasulova Manirakhon; Boltaboev Bakhadir (E3S Web of Conferences, 2024)
The results of experimental investigations into the features of the roller shredder that breaks down plowed land one by one are presented in this article. This allowed for the determination of the optimum roller parameter values and the examination of the shredder type selection. According to experimental research, selecting the right type of roller is primarily responsible for guaranteeing that the field surface is completely treated. Typically, these rollers are working parts with slats, gear-slats, or rods for installation on a reel that provide moisture feeding at the level necessary for germination in compliance with agrotechnical requirements. Slatted, toothed-slatted, and rod roller shredders with comparable diameters were designed and used in experimental investigations to confirm the results that we had acquired. In experimental studies, after using different constant diameter roller shredder, the influence of soil on the degree of abrasion, its density and drag resistance was studied. To reduce the influence of various variable factors on the results obtained, the experiments were carried out on a specially prepared agricultural background, which was first plowed and then leveled. In order to test the theoretically based parameters of the roller shredder selected for experimental research in the field, a fixed-diameter roller shredder base with a coverage width of 1.5 m and strips with gear strips and rod strips that can be installed on them were developed and prepared. Based on the results of experimental studies, the following can be noted: in order for the quality and density of soil abrasion to meet agrotechnical requirements, and the tensile resistance of the coil to be minimal, the roller shredder must be with a slatt.